Unsteady boundary layer flow due to a stretching surface in a rotating fluid - Nazar, Roslinda; Amin, Norsarahaida; Pop, Ioan (Elsevier Ltd, 2004)
The induced unsteady flow due to a stretching surface in a rotating fluid, where the unsteadiness is caused by the suddenly stretched surface is studied in this paper. After a similarity transformation, the unsteady Navier–Stokes equations have been solved numerically using the Keller-box method. Also, the perturbation solution for small times as well as the asymptotic solution for large times, when the flow becomes steady, has been obtained. It is found that there is a smooth transition from the small time solution to the large time or steady state solution